Peran Pemerintah Desa Dalam Pemberdayaan Masyarakat Petani Untuk Menciptakan Petani Unggul Di Desa Rambah Hilir Tengah Guna Mendukung Ketahanan Pangan - Sahara, Wiwin; Seprini; Anwar, Arfianti Novita (Gapenas Publisher, 2025)
This study aims to analyze the role of the village government in empowering farming communities to create superior farmers in Rambah Hilir Tengah Village to support food security. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of this study show that in the aspect of the regulator, the village government does not make rules regarding the empowerment of farming communities, but only realizes the rules that have been issued by the central government, as well as the lack of public knowledge about clear rules regarding guidelines for empowerment to farming communities. In the aspect of dynamizers, the sub-indicators are not said to be optimal as a whole, there are obstacles such as limited support personnel and lack of technical training, and the village government has not played an active role in conducting field visits. The role of the village government as a facilitator in the provision of seeds, fertilizers and production facilities and infrastructure that have been running in accordance with the needs of the farming community. The empowerment of the farming community in Rambah Hilir Tengah Village is still in the formation stage and has not been fully optimal in creating superior farmers. The food security condition of the community in Rambah Hilir Tengah Village is at a level that is still vulnerable and not yet fully strong.